Dampak Pemasaran Influencer, Interaksi Pelanggan, dan Iklan Digital terhadap Citra Merek di Industri Pariwisata Bali - I Wayan Adi Pratama (Jurnal Bisnis dan Manajemen West Science, 2024)
This study examines the impact of influencer marketing, customer interaction, and digital advertising on the brand image of Bali's tourism industry. A quantitative approach was employed, involving 190 respondents who were surveyed using a structured questionnaire. Data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) to evaluate the relationships between the constructs. The results reveal that influencer marketing has the strongest positive impact on brand image, followed by customer interaction and digital advertising. The combined effects of these dimensions explain 68% of the variance in brand image, highlighting the importance of an integrated digital marketing approach. These findings contribute to the literature on tourism marketing and offer practical insights for stakeholders to enhance Bali's brand image through strategic use of influencer campaigns, interactive customer engagement, and targeted digital advertisements.